An acclimatization period in a cage promotes site fidelity of hatchery-reared dusky groupers to the release areas - Silva, AF (2025)
The influence of an in-situ acclimatization period of five weeks, seeking the settlement and fidelity of hatchery-reared dusky groupers (Epinephelus marginatus) to the release sites in restocking actions, was tested using acoustic biotelemetry. Eight tagged adult groupers were submitted to the wild conditions in a fish farm cage, while seven remained in the hatchery and tagging location until they were all released. Ten months later, half of the acclimatized groupers were still present in the release site, while all the non-acclimatized rapidly dispersed. These results show that an in-situ acclimatization period of five weeks promotes the establishment and site fidelity of hatchery-reared dusky groupers, contributing to successful restocking.